Effect of chromium-doping on the crystallization and phase stability in anodized TiO2 nanotubes - Low, It Meng; Albetran, H.; De La Prida, V.; Manurung, P.; Ionescu, M. (2013)
Production of limitless hydrogen fuel by visible light splitting of water using the photoelectrochemical technology is cost-effective and sustainable. To make this an attractive viable technology will require the design of TiO 2 photocatalyst capable of harnessing the energy of visible light. One possible solution is the doping of TiO2 to reduce its band gap. In this paper, the effect of Cr-doping by ion-implantation on the crystallisation and phase stability of TiO2 nanotubes at elevated temperature is described. The effect of Cr-doping on the resultant microstructures, phase changes and composition depth profiles are discussed in terms of synchrotron radiation diffraction, scanning electron microscopy, and ion-beam analysis by Rutherford backscattering spectrometry.